Effects of Disruptive Inclusions in Sandwich Core Lattices to Enhance Energy Absorbency and Structural Isolation Performance - Wadee, M. Ahmer; Phillips, Andrew T. M.; Bekele, Adam (Frontiers in Materials, 2020)
The energy absorption and structural isolation performance of axially-compressed sandwich structures constructed with stiff face plates separated with an auxetic lattice core metamaterial is studied. Advances in additive manufacturing increasingly allow bespoke, carefully designed, structures to be included within the core lattice to enhance mechanical performance. Currently, the internal structure of the lattice core is deliberately disrupted geometrically to engineer suitable post-buckling behaviour under quasi-static loading. The desirable properties of a high fundamental stiffness and a practically zero underlying stiffness in the post-buckling range ensure that energy may be absorbed within a limited displacement and that any transfer of strain to an attached structure is minimized as far as is feasible. It is demonstrated that such disruptions can be arranged to enhance the panel performance. The concept may be extended to promote cellular buckling where the internal lattice buckles with densification occurring at defined locations and in sequence to absorb energy while maintaining a low underlying mechanical stiffness.